Pengaruh promosi, lokasi, dan kualitas layanan terhadap keputusan pembelian nasabah Bank Mandiri Surabaya - Muhammad Fajar Fahrudin; Emma Yulianti (Journal of Business & Banking, 2015)
Today, competition in banking sectors has been very tight, and therefore, in order the banks can survive they have to provide excellent services. Besides, they should also pay attention to the promotion activity, location, and quality of service so that they can attract customers. This study attempts to investigate the effect of promotion, location, and service quality on customers buying decision in Bank Mandiri Surabaya. The sample consists of 74 customers of Bank Mandiri Surabaya selected through the judg-ment sampling technique. Regression analysis with SPSS software was used for data analysis and hypotheses testing. The results show that there effect of promotion and location on customers buying decision in Bank Mandiri Surabaya is not significant. However, service quality has positive and significant effect on customers buying deci-sion in Bank Mandiri Surabaya. The finding of this study suggests that Bank Mandiri Surabaya should pay attention to service quality in order to increase their customer saving.